Pemisahan Waktu Pemilu dan Pilkada Pasca Putusan MK No. 135/Puu-Xxii/2024: Kajian atas Prinsip Efesiensi dan Kedaulatan Rakyat Menurut Perspektif Siyasah Dusturiyah - Karo-Karo, Mursyidan Muzadi; Irwansyah, Irwansyah (Kartika: Jurnal Studi Keislaman, 2025)
The Constitutional Court Decision Number 135/PUU-XXII/2024 introduces a fundamental change to Indonesia’s electoral system by mandating a separation in the timing of national elections and regional head elections. This study aims to analyze the rationale and normative implications of the decision from the perspective of siyāsah dustūriyyah, particularly in relation to the principles of efficiency and popular sovereignty. The research employs a qualitative method based on library research, examining statutory regulations, Constitutional Court decisions, classical and contemporary fiqh siyāsah literature, and relevant academic works. The findings indicate that the separation of election schedules constitutes a form of constitutional reconstruction intended to enhance the effectiveness of electoral administration, reduce excessive administrative burdens, and improve the quality of public political participation. From the perspective of siyāsah dustūriyyah, this policy aligns with the principles of maṣlaḥah and governmental stability, as emphasized by classical Islamic scholars regarding the state’s obligation to regulate power in order to ensure continuity of governance and protection of citizens’ rights. Furthermore, the decision strengthens popular sovereignty by providing voters with a more proportional and effective space to determine their representatives and leaders